2020
DOI: 10.1177/1756284820934327
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent granulomatous cheilitis associated with Crohn’s disease successfully treated with ustekinumab: case report and literature review

Abstract: Granulomatous cheilitis, characterized by persistent inflammation of the lips and a granulomatous histology, is sometimes associated with Crohn’s disease and is a therapeutic challenge. Reported evidence indicates treatment with an anti-TNF agent (mainly infliximab) is the most recommended therapeutic option after failure of conventional treatments. The clinical case reported the effectiveness of ustekinumab, a monoclonal antibody against interleukins 12/23, to induce the remission of severe and recurrent gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This appears to be the first reported case of VDZ leading to remission, and adds to the two recently published cases of UST inducing remission in OFG + CD. 23,24 This shows the importance of targeting the underlying intestinal CD in treating OFG. Interestingly, UST has also recently been shown to be useful for another extraintestinal granulomatous condition, metastatic CD [MCD]: nine cases of MCD were treated with UST, and all responded with the first or second dose, with five achieving remission in a median time of 5 months.…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be the first reported case of VDZ leading to remission, and adds to the two recently published cases of UST inducing remission in OFG + CD. 23,24 This shows the importance of targeting the underlying intestinal CD in treating OFG. Interestingly, UST has also recently been shown to be useful for another extraintestinal granulomatous condition, metastatic CD [MCD]: nine cases of MCD were treated with UST, and all responded with the first or second dose, with five achieving remission in a median time of 5 months.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, ustekinumab, a monoclonal antibody targeting the p40 subunit of IL-12/IL-23, has shown efficacy in managing OCD as seen in the current case. 19,20 The variable response of CD to classical or biologic treatment options reflects a complex immunopathological nature of the disease and entails further research into this area.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who have had a prior infusion reaction to infliximab, certolizumab combined with methotrexate has recently been shown to resolve the cutaneous lesions. Recent studies indicated treatment with an anti-TNF agent (mainly ustekinumab) as the most recommended therapeutic option for granulomatous cheilitis (with or without CD) after failure of conventional treatments 11…”
Section: Treatmentmentioning
confidence: 99%